Power in Madness : a critical investigation into the musical representation of female madness in the mad scenes of Donizetti’s ‘Lucia’ from Lucia di Lammermoor (1835) and Thomas’s ‘Ophélie’ from Hamlet (1868) - Panebianco-Warrens, Clorinda Rosanna (University of Pretoria, 2016)
Mini Dissertation (MMus)--University of Pretoria, 2016.